Economic and Legal Analysis of Accountability Criminal Power of Attorney Budget in Case Action Criminal Corruption - Junaidi Lubis; Faziatul Amillia Mohamad Basir; Debi Masri; Muammar Rinaldi; Achmad Taufiq (Outline Publisher, 2024)
Action criminal Corruption in Indonesia is widespread in society. Its development Keep going increase from year to year although so the number of officials who were convicted Because corruption However it seems like the officials No Once Afraid will threat punishment criminal said. Increasing act criminal corruption that is not under control will bring disaster, not only against life economy national but also in life nation and state in general. Action criminal corruption is violation to right social and rights economy society. Action criminal corruption has become a an extraordinary crime usual. Verdict criminalization to perpetrator act criminal corruption, not in accordance with the provisions Law No. 20 of 2001. The judge has not yet professional in operate his duties, because the judge is figure the determining center how the trial process works run even in hand Judge for yourself go out a the decision that will be determine fate furthermore for a human beings who have do a crime act criminal corruption.